Recognition of Anemia in Elderly People in a Rural Community Hospital - Shiho Amano (MDPI AG, 2021)
Anemia in the elderly is a common disease associated with increased mortality and hospitalization rates. It is not clear how adequately elderly patients are assessed and treated in actual clinical practice. This study clarifies the frequency of anemia recognition before assessment and the factors related to recognition among older people in a rural community hospital. This cross-sectional study evaluated 156 elderly patients aged > 65 years. Data on several different variables were collected from patient medical records. Anemia was defined as a hemoglobin level < 11 g/dL. Patients were classified into “anemia recognition” and “no anemia recognition” groups. Statistical analysis of the data included multivariable logistic regression to examine the association between anemia recognition and other factors. The anemia recognition group comprised 63 (40.4%) patients. Age was significantly associated with the recognition of anemia (adjusted odds ratio = 0.70, 95% confidence interval: 0.53–0.92, p = 0.011). Appropriate medical care should be provided to the elderly; however, it may be limited according to age.